2020
DOI: 10.38001/ijlsb.636695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atrazine and Glyphosate on Soil Carbon Mineralization

Abstract: Tarımsal ekosistemlerde yabancı otların kontrolünde en çok tercih edilen yöntemlerden birisi herbisit kullanımıdır. Mikrobiyal aktive toprakta herbisitlerin davranışlarını belirleyen en önemli faktörlerdendir. Karbon mineralizasyonu toprak kalitesinin biyolojik indikatörlerinden olup topraktaki tüm canlıların hayati faaliyetlerini sürdürebilme kapasitesini yansıtmaktadır. Bu derlemede tarım alanlarında yabancı ot kontrolünde en fazla kullanılan bileşikler olan atrazine ve glyphosate'ın toprakta karbon minerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In a study by Baćmaga et al [20], the count of heterotrophic bacteria increased after the application of chlorothalonil at recommended (0.166 mg kg −1 ), 10-fold and 100-fold field rates to sandy loam and loamy sand soil. This fits with the finding of this study, where carbon mineralization increased in line with the application of the fungicide cyprodinil at recommended, 2-fold, and 4-fold field rates [45]. Baelum et al [46] showed that bacteria expressing tfdA or tfdA-like genes were able to degrade MCPA.…”
Section: Mineralization (Min)supporting
confidence: 90%
“…In a study by Baćmaga et al [20], the count of heterotrophic bacteria increased after the application of chlorothalonil at recommended (0.166 mg kg −1 ), 10-fold and 100-fold field rates to sandy loam and loamy sand soil. This fits with the finding of this study, where carbon mineralization increased in line with the application of the fungicide cyprodinil at recommended, 2-fold, and 4-fold field rates [45]. Baelum et al [46] showed that bacteria expressing tfdA or tfdA-like genes were able to degrade MCPA.…”
Section: Mineralization (Min)supporting
confidence: 90%
“…In addition, it is used in the control of broad-leaved weeds in corn and sugar cane fields around the world and has been reported to be one of the most detected chemicals in water resources near agricultural areas. It has been found that Atrazine is toxic to many aquatic organisms, even at low concentrations, and causes hermaphroditism in frogs (Kocak, 2020). 95% of the antibacterial pesticides triclosan and triclocarban are used in residences.…”
Section: Pesticidesmentioning
confidence: 99%